Banking efficiency in dollarized Latin America countries during 2007-2021 - Guachamin Guerra, Marcela Elizabeth (2022)
This research contributes to the literature and the monitoring of banks in the absence of studies focused on bank efficiency in the three dollarized countries. A two-stage analysis is proposed, in which a non-parametricmethodology called Data Envelopment Analysis (DEA) is applied to a sample of 138 banks to calculate a comparative measure of bank efficiency. In the second stage, the determinants of bank efficiency are analyzed by means of a panel data regression model with a set of financial, economic, and regulatory data as explanatory variables. The results suggest that size, solvency, liquidity, profitability, market concentration, GDP and the regulatory environment are determinants of bank efficiency for the three dollarized countries.